Defining optimal elevation thresholds for mangrove restoration through dynamic tidal simulation: Evidence from morphological and physiological assessment of five species in Zhanjiang Bay, China - Jianjian Huang; Bing Yang; Xin Zhou; Jie Chen; Suqing Liu; Kangyi Deng; Xiuxuan Lin; Yiting Chen; Ruixuan Wang; Yuzhong Zheng; Qinghan Wu; Hui Zhu; et al. (Ecological Engineering, 2026)

Transcriptional activation of TcToll9 to exogenous bacteria in the larvae of Tribolium castaneum - Qiuying He; Shiyuan Li; Hui Lv; Ruixuan Lin; Xintong Wu; Jisheng Liu (Journal of Stored Products Research, 2026)

Two-level energy storage semi-interpenetrating hydrated salt gel for battery cooling and thermal runaway propagation mitigation - Rui Wei; Yuhan Xiao; Jianfeng Wang; Fuqiang Wang; Di-Lin Chen; Bowei Chen; Zipeng Su; Yongkai Jia; Ruixuan Qiu; Yiqun Liu; Quanqing Yu; Fen Liu (Chemical Engineering Journal, 2026)

Hot-Spot-Guided Generative Deep Learning for Drug-Like PPI Inhibitor Design - Heqi Sun; Jiayi Li; Yufang Zhang; Shenggeng Lin; Junwei Chen; Hong Tan; Ruixuan Wang; Xueying Mao; Jianwei Zhao; Rongpei Li; Dong-Qing Wei (Interdisciplinary Sciences: Computational Life Sciences, 2026)

Radially graded porosity in La-based OCM catalysts: a CFD-driven framework for optimizing reaction-diffusion dynamics at the single-particle scale - Ruixuan Li; Yongxiang Gao; Jianjian Dai; Xi Gao; Minggui Lin; Litao Jia; Debao Li (Chemical Engineering Journal, 2025)

Nanocellulose from agro-industrial wastes: A review on sources, production, applications, and current challenges - Yefan Wang; Ziyan Wang; Yu Lin; Yiming Qin; Ruixuan He; Mingxiao Wang; Quancai Sun; Ye Peng (Food Research International, 2024)

Carboxymethyl cellulose-based supramolecular hydrogel with thermo-responsive gel-sol transition for temporary plugging of oil pipeline in hot work - Ziteng Yang; Ruixuan Ni; Yang Yang; Jie Qi; Xingyu Lin; Yong Zhang; Li Wang; Yuanpeng Wu; Xiaojiang Li; Hongsheng Lu (Carbohydrate Polymers, 2024)

Effects of dietary sodium acetate on intestinal health of juvenile Trachinotus ovatus based on multi-omics approach - Pengwei Xun; Chuanpeng Zhou; Xiaolin Huang; Zhong Huang; Wei Yu; Yukai Yang; Jianbin Huang; Yang Wu; Ruixuan Wang; Heizhao Lin (Aquaculture, 2023)

Proteomic differences between Vibrio tubiashii strains with high- or low-virulence levels isolated from diseased ivory snail Babylonia areolata - Ruixuan Wang; Xiaojing Liu; Jiangyong Wang; Huizhu; Xiaozhi Lin; Jingfeng Sun; Hongli Mou; Ting Zhang; Xilan Ma (Aquaculture International, 2022)

Microplastics in Mollusks: Research Progress, Current Contamination Status, Analysis Approaches, and Future Perspectives - Ruixuan Wang; Hongli Mou; Xiaozhi Lin; Hui Zhu; Bing Li; Jiangyong Wang; Muhammad Junaid; Jun Wang (Frontiers in Marine Science, 2021)
Plastic fragments < 5 mm, known as microplastics (MPs), are ubiquitously present in the marine environment. Research on MPs pollution has gradually shifted from field investigations to laboratory studies. With the rapid growth of plastic consumption and the prevalence of aquaculture products, studies on marine MPs have focused on key marine species, such as mollusks. This review summarizes the recent knowledge including 77 important relevant literatures (from 2010 to 2021) on MPs contamination in mollusks with the objectives of (1) elucidating the current status of MPs pollution levels in mollusks, (2) highlighting the main methods and techniques for separation, extraction, and identification of MPs in soft tissues of bivalves and (3) presenting the current research progress and future directions. The review visually presents some of the important results in graphic form, which shows that the most common polymer plastics in bivalves are polypropylene, polystyrene, and polyethylene, and the shapes were mainly fiber and threadiness, mollusks are more likely to feed smaller MPs, most of the MPs in bivalves are less than 500 μm, and the abundance of MPs in seawater and the abundance of MPs in mollusks have a positive relationship, etc. This review will provide a comprehensive reference for studies of microplastics in marine organisms and the ecological pollution, and also has scientific guiding significance in the research method.